TIGAR Promotes Tumorigenesis and Protects Tumor Cells From Oxidative and Metabolic Stresses in Gastric Cancer - Liu, Zhenhua; Wu, Yue; Zhang, Yingqiu; Yuan, Menglang; Li, Xuelu; Gao, Jiyue; Zhang, Shanni; Xing, Chengjuan; Qin, Huamin; Zhao, Hongbo; Zhao, Zuowei (Frontiers in Oncology, 2019)
Cancer cells adopt glycolysis to facilitate the generation of biosynthetic substrates demanded by cell proliferation and growth, and to adapt to stress conditions such as excessive reactive oxygen species accumulation. TIGAR (TP53-induced glycolysis and apoptosis regulator) is a fructose-2,6-bisphosphatase that is regulated by p53. TIGAR functions to inhibit glycolysis and promote antioxidative activities, which assists the generation of NADPH to maintain the levels of GSH and thus reduces intracellular reactive oxygen species. However, the functions of TIGAR in gastric cancer (GC) remain unclear. TIGAR expression levels were detected by immunoblotting and immunohistochemistry in gastric cancer samples, along with four established cell lines of GC. The functions of TIGAR were determined by utilizing shRNA-mediated knockdown experiments. The NADPH/ NADP+ ratio, reactive oxygen species, mitochondrial ATP production and phosphorus oxygen ratios were determined in TIGAR-depleted cells. Xenograft experiment was conducted with BALB/c nude mice. TIGAR was up-regulated compared with corresponding non-cancerous tissues in primary GCs. TIGAR knockdown significantly reduced cell proliferation and increased apoptosis. TIGAR protected cancer cells from oxidative stress-caused damages, but also glycolysis defects. TIGAR also increased the production of NADPH in gastric cancer cells. TIGAR knockdown led to increased reactive oxygen species production, elevated mitochondrial ATP production and phosphorus oxygen ratios. The prognosis of high TIGAR expression patients was significantly poorer than those with low TIGAR expression. Taken together, TIGAR exhibits oncogenic features in GC, which can be evaluated as a target for intervention in the treatment of GC.